Bifurcations in a diffusive predator–prey model with predator saturation and competition response. (11th March 2014) - Muniyagounder, S.; Balachandran, K.
<x xml:space="preserve">Abstract</x> A diffusive predator–prey model with predator saturation and competition response subject to homogeneous Neumann boundary conditions is considered in this paper. We find that the spatially homogeneous and non‐homogeneous periodic solutions through all parameters of the system are spatially homogeneous. To verify our theoretical results, some numerical simulations are also carried out. Copyright © 2014 John Wiley & Sons, Ltd.